Comparative Study of Cryotherapy Versus 0.05% Tretinoin Cream for the Treatment of Molluscum Contagiosum in Children - Riaz, Novera; Arfan ul Bar; Khan, Wania Anosh; Zaidi, Syeda Naveen; Fatima, Attiya; Khan, Saba (Indus Journal of Bioscience Research, 2025)
Background: Molluscum contagiosum (MC) is an infection caused by a poxvirus. Although it is a self-limiting condition, active treatment is often necessary to prevent further spread, alleviate symptoms, reduce the risk of scarring, and address cosmetic and social concerns. Methods: A randomised controlled trial was conducted at the Pakistan Emirates Military Hospital’s Dermatology Department from January to June 2024. It compared the safety and efficacy of cryotherapy versus 0.05% tretinoin in treating molluscum contagiosum. Forty patients were enrolled, with random assignment into two treatment groups. Analysis was performed using IBM-SPSS 21.0, with significance set at p ≤ 0.05. Results: The median age for the cryotherapy group was 7 years (range 3-7), compared to 8 years (range 2-8) in the tretinoin group. The cryotherapy group had a higher proportion of males (60.0%) versus the tretinoin group’s 25.0%, while the tretinoin group had more females (75.0%) compared to 40.0% in the cryotherapy group. During the first week, cryotherapy improved lesion counts by 5.8% (from 6.5 ± 3.8), while tretinoin showed a 2.7% improvement (6.8 ± 3.7). Cryotherapy demonstrated superior efficacy over 12 weeks, achieving 100% cure compared to 91.8% with tretinoin. Adverse effects varied, with significant differences in pain, erythema, itching, burning sensation, and erosions. Conclusion: Both cryotherapy and 0.05% tretinoin cream were effective and well tolerated. Cryotherapy led to faster resolution of lesions, typically within 12 weeks, and had manageable side effects. Tretinoin cream showed slower lesion resolution but fewer side effects, making it suitable for recurrent cases and children.